Prosthetic Mitral Valve Thrombosis in Pregnancy: From Thrombolysis to Anticoagulation - Cardoso, G (2015)
INTRODUCTION: Pregnant women with mechanical prosthetic heart valves are at increased risk for valve thrombosis. Management decisions for this life-threatening complication are complex. Open-heart surgery has a very high risk of maternal mortality and fetal loss. Bleeding and embolic risks associated with thrombolytic agents, the limited efficacy of thrombolysis in certain subgroups, and a lack of experience in the setting of pregnancy raise important concerns. CASE REPORT: We report a case of mitral prosthetic valve thrombosis in early pregnancy, which was successfully treated with streptokinase. Ten years later, the same patient had an uneventful pregnancy, throughout which acenocoumarol was maintained. CONCLUSION: With this case we review the prevention (with oral anticoagulant therapy) and treatment of prosthetic valve thrombosis during pregnancy, which is important for both obstetrician and cardiologist.